2022
DOI: 10.3389/fnut.2022.998448
|View full text |Cite|
|
Sign up to set email alerts
|

The changes of umami substances and influencing factors in preserved egg yolk: pH, endogenous protease, and proteinaceous substance

Abstract: The study investigated the changes of nucleotides, succinic acid, and free amino acids amounts in yolk and the causes leading to the changes after pickling to uncover the fundamental umami component of preserved egg yolk. The findings demonstrated that while the contents of 5′-adenosine monophosphate (AMP), 5′-cytidine monophosphate (CMP), 5′-guanosine monophosphate (GMP), 5′-uridine monophosphate (UMP), and succinic acid increased after slightly decreasing aspartic acid (Asp) content in preserved egg yolk inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…TCA-SP is a parameter that indicates the degree of protein decomposition, mainly including small peptides with molecular weight less than 10 kDa; free amino acids; and small amounts of non-protein nitrogen compounds [35]. Yang et al [16] reported that the content of TCA-SP in fermented PNM was increased by 400.37%, which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…TCA-SP is a parameter that indicates the degree of protein decomposition, mainly including small peptides with molecular weight less than 10 kDa; free amino acids; and small amounts of non-protein nitrogen compounds [35]. Yang et al [16] reported that the content of TCA-SP in fermented PNM was increased by 400.37%, which was consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Wuchuan is located in Guizhou Province, southwestern China ( Figure 1 ). Wuchuan Hg mine is one of the largest Hg mines in Guizhou Province, with a Hg production history of about 400 years ( 20 , 21 ). Despite the cessation of mining for 20 years, local environmental Hg levels (in soil, water, and rice) are still evidently higher than the standard limitation ( 6 ).…”
Section: Methodsmentioning
confidence: 99%